2008
DOI: 10.1111/j.1365-2702.2008.02462.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Visible‐ness’: the nature of communication for children admitted to a specialist children's hospital in the Republic of Ireland

Abstract: Aim. This article presents the core concept of 'visible-ness' that emerged from an ethnographic study, which explored the nature of communication, for children (for ease of reading children refers to children and young people), admitted to a children's hospital in the Republic of Ireland. Background. The importance of engaging with both child and family has been espoused as fundamental in promoting 'family'-centred care. To date, studies have almost exclusively explored parents' and nurses' perspectives of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 38 publications
4
60
1
1
Order By: Relevance
“…In the contemporary study, children appreciated handing over responsibility to their parents at times and sharing decision-making with them. This finding is in accordance with previous studies by Lambert et al [24,25], who found that children want to waver between being a “passive bystander” and an “active participant” in the communication process, depending on the situation. Children often want to be involved and to participate in and to contribute to shared decision-making.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the contemporary study, children appreciated handing over responsibility to their parents at times and sharing decision-making with them. This finding is in accordance with previous studies by Lambert et al [24,25], who found that children want to waver between being a “passive bystander” and an “active participant” in the communication process, depending on the situation. Children often want to be involved and to participate in and to contribute to shared decision-making.…”
Section: Discussionsupporting
confidence: 93%
“…During the last few decades, studies have been performed with instead of on children. These studies have provided new and important knowledge about, for instance, children’s experiences with regard to the hospital environment [21-23], communication [24,25], consultation [26], short-term illnesses [27,28], chronic illnesses in general [29], and diabetes [30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…In these situations, the parent did always repeat the information to the HCP; however, if they had chosen not to, RN’s role would have been further challenged, as to act in the child’s and/or families best interests RN would have needed to have actively intervened and informed the MDT of the concerns. Additionally, as Lambert et al [50] suggest, the dividing line between informal discussions with participants and more formal interviews is hard to differentiate at times, reinforcing the need in our study for RN to regularly remind participants of her role as a researcher.…”
Section: Methodsmentioning
confidence: 93%
“…One concern raised in relation to this type of research is that the presence of a researcher may potentially disturb natural interactions and trigger a change in the behaviour of those being observed [50]. Carnevale et al [6] expressed concerns that observations could be obtrusive and/or psychologically distressing for some participants.…”
Section: Methodsmentioning
confidence: 99%
“…Lambert et al (46) found that children's participation in the communication process was based on the children's ability to articulate their desire to engage in the communication process, health professionals' attitudes towards communication with children and the hospital environment itself.…”
Section: Communication With Paediatric Patientsmentioning
confidence: 99%